Controle físico-químico das folhas de Dodonaea viscosa (L.) Jacq., atividade antioxidante e anti-inflamatória - Ercolani, Cauriane Medianeira (2010)
Dodonaea viscosa (Linnaeus) Jacquin (Sapindaceae) is a shrub foun in Brazil, the SP RS. It is a native species in RS, popularly known as red broom, broom-offield. Within its leaves flavonoids, saponins, essential oils, mucilage, gums, coumarins, cardioactive and organic acids. Indicated to treat inflammation, pain and fever. The aim of this study was establish standards of quality and purity of the drug plant throuh physical-chemical analysis and assay of phenolic compounds to determine the antioxidant activity DPPH and antiinflammatory activity in rat models. According to the results obtained in the crude extract to 70% of the leaves of D. viscosa that the physical-chemical analysis allowed to establish quality control parameter for D. viscosa wich presents significant antiinflammatory activity antioxidant, wich can be attributed to the concentration of phenolic compounds.